The Study of the Progress of School Education In India: Recent Progress and International Recognition of School Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Education in India is matter of major concern for the government ofIndia. India, with its variety fascinates one and all. Indian Education hasnewly gained world acknowledgment. Many students from foreign countries areeyeing the country for gaining higher qualifications. This paper provides anoverview of progress of school education in India. India has made best progressin terms of sending children to school in the last five years, according to arecent report of the United Nations Educational, Scientific and CulturalOrganization (Unesco).